Case report: Apalutamide-induced severe lethal cutaneous adverse effects in China - Wang, Qi; Cao, Huali; Zhang, Xuetong; Wu, Huifeng; Tang, Zhuangli (Frontiers in Immunology, 2024)
Introduction: Apalutamide is a novel agent for castration-resistant prostate cancer while skin rashes are the most common untoward reactions. Up to now, most of the reported dermatologic adverse events (dAEs) allocated to mild and moderate with a fair prognosis. Herein, we report a case series of severe dAEs in China caused by apalutamide.The four patients all developed severe and lethal drug eruptions including Stevens-Johnson syndrome and toxic epidermal necrolysis with a mean incubation period of 40 days. On the basis of the medical condition, all the patients were suggested to withdraw apalutamide and three of them recovered. Of note, attempts of rechallenges of apalutamide may be fatal.The incidence of dAEs in previously conducted clinical trials exceeded 20%, with maculopapular rashes being the most common feature. However, the incidence and severity varied in different geographic regions and ethnicities.Inadequate attention was paid to severe cutaneous adverse reactions. Long latency may easily lead to the misdiagnosis of dAEs, and immediate withdrawal of apalutamide is the cornerstone of therapies.Special and adequate attention should be paid to apalutamideattributed severe cutaneous adverse effects. Besides, the prognosis of severe drug eruptions may be disappointing, and in-time withdrawal is vital.